Effectiveness of Al-Qur'an Based Learning to Improve Students' Spiritual Literacy in Islamic Elementary Schools - Supriatna, Asep (Journal of Modern Islamic Studies and Civilization, 2025)
Al-Qur'an-based learning has an important role in forming students' spiritual literacy from an early age, especially in the modern era. This spiritual literacy includes the ability to understand, internalize, and practice the values ​​of the Al-Qur’an in everyday life. This research aims to measure the effectiveness of Al-Qur'an-based learning in improving students' cognitive, affective, and psychomotor aspects at Madrasah Ibtidaiyah Tarbiyatul Athfal. This research uses a qualitative descriptive method with a survey approach. Data was collected through interviews, observations, and tests on students. Data analysis techniques involve simple statistical calculations to evaluate achievements in each aspect of learning. Data validity is obtained through triangulation of sources and methods. The research results showed that cognitive aspects, such as reading and memorizing verses of the Al-Qur'an, had the highest achievement, with 90% of students able to read well and 83% successful in memorizing. However, achievements in the affective aspect, namely understanding the meaning of verses and relating them to daily life, only reached 60% and 50%. In the psychomotor aspect, 67% of students have practiced the values ​​of the Al-Qur’an, such as being honest and disciplined. These findings indicate that Al-Qur'an-based learning methods need to be more innovative, using interactive media, in-depth reflection, and an applied approach. The implication of this research is the importance of training teachers to develop more creative and relevant teaching methods.